Risk Factors for Pelvic Organ Prolapse and its Recurrence: A Systematic Review. Issue 1 (January 2016) - Vergeldt, Tineke F. M.; Weemhoff, Mirjam; IntHout, Joanna; Kluivers, Kirsten B.
Abstract : Obstet Gynecol Surv 2016;71(1):21–22 Pelvic organ prolapse (POP) is multifactorial in etiology. Throughout a woman's lifespan, interactions occurring between combinations of anatomical, physiologic, genetic, lifestyle, and reproductive factors contribute to pelvic floor dysfunction.